2009
DOI: 10.1007/s10549-009-0640-6
|View full text |Cite
|
Sign up to set email alerts
|

Combined genetic effect of CDK7 and ESR1 polymorphisms on breast cancer

Abstract: Breast cancer development is related to genes regulating cell cycle progression such as CCND1, CDK7, and ESR1. We conducted a hospital-based case-control study to evaluate the role of genetic polymorphisms in these genes in breast cancer development among Korean women. Questionnaire data and samples were obtained from 864 incident breast cancer cases and 723 controls recruited from 1995 to 2002. Four single nucleotide polymorphisms (SNPs) in three genes were genotyped by matrix-assisted laser desorption/ioniza… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
18
1

Year Published

2011
2011
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 22 publications
(19 citation statements)
references
References 25 publications
0
18
1
Order By: Relevance
“…In agreement with this, potentially critical dysregulation of ER-α expression has been suggested to be involved in pathological processes of several human diseases including breast cancer (Shin et al, 2003). Recently, it has been reported that the abnormal ER-α expression is mainly caused by genetic polymorphisms of ESR1 gene and the transcript variants, different in their 5' UTRs, can stimulate growth and mediate differentiation of normal mammary tissue through high affinity binding to ERs (Jeon et al, 2010). Therefore, the expression of ER-α and its downstream signaling are likely altered by such mechanism, and it comes out that higher expression of circulating ER-α, as well as prolonged estrogen exposure, has been associated with increased breast cancer risk (Key et al, 2002).…”
Section: Discussionmentioning
confidence: 71%
See 1 more Smart Citation
“…In agreement with this, potentially critical dysregulation of ER-α expression has been suggested to be involved in pathological processes of several human diseases including breast cancer (Shin et al, 2003). Recently, it has been reported that the abnormal ER-α expression is mainly caused by genetic polymorphisms of ESR1 gene and the transcript variants, different in their 5' UTRs, can stimulate growth and mediate differentiation of normal mammary tissue through high affinity binding to ERs (Jeon et al, 2010). Therefore, the expression of ER-α and its downstream signaling are likely altered by such mechanism, and it comes out that higher expression of circulating ER-α, as well as prolonged estrogen exposure, has been associated with increased breast cancer risk (Key et al, 2002).…”
Section: Discussionmentioning
confidence: 71%
“…Neither of Einarsdottir et al and Tsezou et al observed significant difference in the frequency distribution of corresponding ESR1 gene mutations between patients and controls and supported a strong association between variants in the ESR1 genes and breast cancer susceptibility, tumor characteristics or survival (Einarsdottir et al, 2008;Tsezou et al, 2008). It is notable that Jeon et al similarly came to the conclusion that no significant correlation existed between breast cancer risk and the genetic polymorphisms of ESR1, but when ESR1 P325P was analyzed together with CDK7, women carrying both the CDK7 TT and ESR1 P325P CC genotypes showed increased breast cancer risk (Jeon et al, 2010). The controversial results of the prognostic value of ESR1 are probably due to the small sample size and the differences between studies, such as ethnic backgrounds, geographical locations, and the baseline characteristics of the included patients (age, histological type, menopausal status, differentiation or tumor stage) (Li et al, 2010).…”
Section: Menopausal Status Modifies Breast Cancer Risk Associated Witmentioning
confidence: 91%
“…CDK7 and 9 protein levels and kinase activities are elevated in various tissues and dysregulation of their function correlate with aberrant transcription profiles observed in lung and breast adenocarcinoma, endometrial carcinoma, leukemia, lymphoma, multiple myeloma, and neuroblastoma (23)(24)(25)(26)(27)(28)(29)(30). The CDK inhibitor flavopiridol has shown both preclinical and clinical activity, especially in hematologic malignancies (31)(32)(33)(34)(35)(36).…”
Section: Introductionmentioning
confidence: 99%
“…The expression of CDK 6 is also altered in oral cancer (Poomsawat et al 2010). CDK7 polymorphisms have been shown to have an eVect on breast cancer (Jeon et al 2010).…”
Section: Introductionmentioning
confidence: 99%